2020
DOI: 10.1177/1477878520912997
|View full text |Cite
|
Sign up to set email alerts
|

What makes a response to schoolroom wrongs permissible?

Abstract: Howard’s moral fortification theory of criminal punishment lends itself to justifying correction for children in schools that is supportive. There are good reasons to include other students in the learning opportunity occasioned by doing right in response to wrong, which need not exploit the wrongdoing student as a mere means. Care ethics can facilitate restorative and problem-solving approaches to correction. However, there are overriding reasons against doing so when this stigmatises the wrongdoing student, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Furthermore, an appreciation of the wide range of measures that might in principle count as punitive should mitigate the worries of Martin about the idea that punishment might play an ineliminable role in schools. This leaves open a wide range of questions about the circumstances in which punitive responses to classroom wrongs ‐ and other wrongdoing in the school community ‐ might be justifiable (Brown Coverdale, 2020).…”
Section: Non‐standard Subjects Of Punishmentmentioning
confidence: 99%
“…Furthermore, an appreciation of the wide range of measures that might in principle count as punitive should mitigate the worries of Martin about the idea that punishment might play an ineliminable role in schools. This leaves open a wide range of questions about the circumstances in which punitive responses to classroom wrongs ‐ and other wrongdoing in the school community ‐ might be justifiable (Brown Coverdale, 2020).…”
Section: Non‐standard Subjects Of Punishmentmentioning
confidence: 99%
“…This translates into teachers creating a pedagogical environment that helps educating fundamental social values and norms, both during lecturing and beyond (Husu & Tirri, 2007). Importantly, teachers also follow such educational principles in the face of student misbehavior (Coverdale, 2020;Goodman, 2020;Hand, 2020;Liu, 2017). For example, it has been suggested that teachers respond in such situations "for a myriad of reasons, including but not limited to moral education of students, maintaining safety, and creating an environment conducive to learning" (Thompson et al, 2020, p. 79).…”
Section: Teachers' and Students' Punishment Goalsmentioning
confidence: 99%
“…Thus, for example, they do not engage with non‐ideal questions of morality in the classroom, such as which forms of punishment, if any, teachers should use in response to a student who is doing wrong (cf. Coverdale, 2020). Brighouse and Gina (2014, p. 109) have argued that this lack of attention to non‐ideal theory can result in “inadequate guidance in the nonideal circumstances that we actually face.” 3 Therefore this article also highlights central practical implications that the various conceptions of educational justice have under non‐ideal circumstances.…”
Section: Introductionmentioning
confidence: 99%